UPAYA GURU BIMBINGAN DAN KONSELING DALAM MEMBANGKITKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 2 PANGKALAN KURAS KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Awaluddin ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this study is the lack of student motivation. This study aims to increase students' motivation. This research is a class act, Based on the results through the processing of the questionnaire, the efforts of guidance teachers to motivate students overall belajarj included into the category Good. Based on the collection of data obtained from the questionnaire to 30 students with 12 questions can be authors conclude that the ultimate answer is SS (very often). Therefore it can be considered that the guidance teacher efforts to motivate student learning in SMPN 2 Pangkalan Kuras Kecamatan Pangkalan Kuras "Pretty Good".